Evaluasi Penerapan Delapan Standar Nasional Pendidikan (SNP) Di Sekolah Menengah Teologi Benfomeni Kapan : Studi Kasus dan Implikasinya Terhadap Akreditasi - Christiana, Marya Dorince (JPT : Jurnal Pendidikan Tematik, 2025)
School accreditation is an educational quality assurance system that functions to assess the feasibility and quality of educational provision in various institutions, including Senior High Schools (SMA). This study reviews the basic concepts, objectives, assessment components, and stages of senior high school accreditation in Indonesia, which are guided by the National Education Standards (Standar Nasional Pendidikan/SNP). The Christian Theological Senior High School (Sekolah Menengah Teologi Kristen/SMTK) is a formal secondary education institution under the Ministry of Religious Affairs that integrates general education with distinctive Christian theological characteristics, aiming to develop students who are faithful, of strong character, and academically competent at a level equivalent to SMA. To ensure its quality, SMTK is required to undergo accreditation. This literature review indicates that accreditation plays a strategic role in ensuring the quality of educational services in SMTK, in alignment with the National Education Standards (SNP) while simultaneously maintaining the distinctive standards of Christian religious education. The school accreditation process (for both public and private schools) functions as a mechanism for evaluating and improving educational quality. The stages begin with preparation (the formation of a team, socialization, training, data/document collection, and the preparation of a self-evaluation report), followed by the completion of accreditation instruments covering three main aspects: management, educational/learning processes, and facilities and infrastructure. Accreditation provides formal recognition of school quality and encourages continuous improvement and innovation. After the visitation, the assessment is conducted through data verification, observation, interviews, and documentation of facilities by assessors. The assessors analyze school performance based on national standards and produce a report that determines the accreditation status (A, B, C, or Not Accredited), along with recommendations for improvements to be implemented.